T17b murine embryonal endothelial progenitor cells can be induced towards both proliferation and differentiation in a fibrin matrix - Bleiziffer, Oliver; Horch, Raymund E.; Hammon, Matthias; Arkudas, Andreas; Naschberger, Elisabeth; Rath, Subha; Pryymachuk, Galyna; Beier, Justus; Hatzopoulos, Antonis K.; Stürzl, Michael; Kneser, Ulrich (Journal of Cellular and Molecular Medicine, 2009)
Endothelial progenitor cells (EPC) may enhance blood vessel formation in a variety of clinical settings such as ischaemia and tumour angiogenesis as well as in tissue-engineered matrices. In the present study, we cultured a murine endothelial progenitor cell line, T17b, in vitro in cell culture as well as in an FDA-approved fibrin matrix and investigated cell proliferation, differentiation and secretion patterns of the angiogenic growth factor VEGF under hypoxia and differentiation. We show that T17b EPC remain viable for at least 8 days in the fibrin matrix where they proliferate and form clusters including lumen-like structures. Proliferation in fibrin clots overlayed with basal medium (BM) was confirmed morphologically and immunohistochemically by positive Ki67 staining, indicating mitotic activity. Significant cell proliferation and Ki-67 expression were absent when cells were incubated with dibutyryl-cAMP and retinoic acid (RA). Incubation with dibutyryl-cAMP and RA stimulated the expression of the EPC differentiation markers von Willebrand Factor (vWF) and VEGF receptor 2 (VEGFR-2), indicating successful differentiation in the fibrin clot. EPC differentiation induced by dibutyryl-cAMP and RA was confirmed in 2-D chamber slide cultures by positive vWF immunostaining, which was absent in BM controls. EPC chamber slides also displayed positive vWF staining when exposed to hypoxia under BM conditions, indicating EPC activation and differentiation could also be induced by hypoxia. Taken together, T17b EPC secrete increased levels of VEGF when submitted to either hypoxia or differentiation and can be differentiated into mature endothelial cells not only in cell and matrigel cultures but also in a fibrin matrix that is FDA approved for clinical application. © 2009 Foundation for Cellular and Molecular Medicine/Blackwell Publishing Ltd.
Created from Fastlane, Scopus look-up
Keywords: Angiogenesis; Embryonal endothelial progenitor cells; Tissue engineering